The Formation of Islamic Hermeneutics - Mourad Laabdi (International Institute of Islamic Thought, 2014)
David Vishanoff’s The Formation of Islamic Hermeneutics is a significant contribution to the study of Islamic legal theory and legal hermeneutics. Vishanoff’s main objective is to examine how Sunni legal hermeneutics became a systematic and institutional discipline. For this purpose, he strives to restore the reception and development of al-Shafi‘i’s (d. 820) legal hermeneutics during the pre-classical period (ninth to eleventh centuries). He presents the imam as the first scholar to have codified an Islamic legal theory and reads him in light of four hermeneutical models: the Zahiri, Mu‘tazili, Ash‘ari and, what he calls, a law-oriented model. The book is organized into seven chapters, five of which are devoted to al-Shafi‘i’s hermeneutics and the four responses to it. Chapter 1 and 7, respectively, serve as analytic introduction and conclusion. The most authoritative source investigated by the author, and to which Chapter 2 is devoted, is al-Shafi‘i’s Al-Risālah fī Uṣūl al-Fiqh. Central to this text is al-Shafi‘i’s argument that a system of law can and should be inferred from revelation: the Qur’an and Sunnah. The Risālah, Vishanoff confirms, is the first work to have raised a consequential hermeneutical question in the Islamic legal theory: How does one reconcile revealed texts with legal rules? Al-Shafi‘i’s solution, one that places the Qur’an’s equivocalness or linguistic ambiguity at the centre of its argument, was one of the most debated legal themes at the time; a deliberation that has largely contributed to the formation of classical uṣūl al-fiqh ...